2016
DOI: 10.1097/hjh.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Hu antigen R is required for NOX-1 but not NOX-4 regulation by inflammatory stimuli in vascular smooth muscle cells

Abstract: Objective NOX-1 and NOX-4 are key enzymes responsible for reactive oxygen species (ROS) generation in vascular smooth muscle cells (VSMC). The RNA-binding protein HuR is implicated in post-transcriptional regulation of gene expression; however, its role regulating NOX is unknown. We investigated transcriptional and post-transcriptional mechanisms underlying angiotensinII (AngII) and interleukin-1β (IL-1β) regulation of NOX-1 and NOX-4 in VSMC and their implications in cell migration. Methods Rat and human VS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…It has also been reported that ROS generation triggered cytoplasmic translocation of HuR, leading to enhancement in activity of TGFβ pathway (ROS-HuR-TGFβ pathway) [ 28 ]. Moreover, HuR was implicated in posttranscriptional regulation of NADPH oxidase-1 (NOX-1), one crucial enzyme for ROS production [ 29 ]. We therefore suspected that modulating HuR might affect the generation of ROS induced by Epi.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that ROS generation triggered cytoplasmic translocation of HuR, leading to enhancement in activity of TGFβ pathway (ROS-HuR-TGFβ pathway) [ 28 ]. Moreover, HuR was implicated in posttranscriptional regulation of NADPH oxidase-1 (NOX-1), one crucial enzyme for ROS production [ 29 ]. We therefore suspected that modulating HuR might affect the generation of ROS induced by Epi.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that NAPDH oxidase (NOX)1 and NOX4 are key enzymes responsible for ROS generation in VSMCs [36]. To understand the source of ROS and to determine the association of Ang II signaling, Klf5, and eIF5α with NOX expression, mouse VSMCs were transfected with expression vectors for Klf5 and eIF5α or small interfering RNA (siRNA) against Klf5 and eIF5α, respectively, and then treated with Ang II for 0, 1, 3, and 5 days, and the expression of NOX1 and NOX4 was detected by RT-qPCR.…”
Section: Inhibition Of the Mitochondrial Fission Decreases Mtros Prodmentioning
confidence: 99%
“…For instance, in rat aortic smooth muscle cells, production of ROS by IL-1β is mediated by NOX4 ( 43 ). Although IL1-β induces its expression ( 44 ), NOX1 does not appear to be involved in IL1-β-induced ROS production ( 43 ). In addition, TGF-β has been shown to induce NOX4 expression as well as ROS production in human arterial smooth muscle cells ( 45 ).…”
Section: Introductionmentioning
confidence: 99%